Prevalence of dental anxiety among transgender women in Malaysia and its associated factor - Said, Abdul Hadi; Mohd, Farah Natashah; Abu Zarim, Khairunnisa; Ibrahim, Nurul Ruziantee; Draman, Samsul (Ektodermal Displazi Grubu, 2021)
The prevalence of dental anxiety among transgender women (TGW) in Malaysia is still unknown. The objective of this study was to determine the prevalence of dental anxiety among TGW and its associated factors. A cross-sectional study was conducted among 100 TGW from 16th-18th August 2019 during a medical camp in Terengganu, Malaysia using universal sampling. A validated Malay version of Modified Dental Anxiety Scale (MDAS) was used to assess the prevalence of dental anxiety among TGW. Bivariate (Chi-square and Mann Whitney tests) and multivariate analysis (Multiple logistic regression) were used to assess the association between dental anxiety and sociodemographic profile. P value of <0.05 was set as statistically significant. One hundred participants included in the study. A fifth of them had history of being discriminated when seeking dental treatments. Eighty-seven percent of the respondents had dental anxiety with a quarter of them had extreme dental anxiety (dental phobia). The percentage of MDAS anxiety scores associated with the use of the drill and intraoral local anaesthetic injection was found to be the highest among other items. However, bivariate and multivariate analysis performed failed to find any significant association between dental anxiety and sociodemographic profile. It is foreseeable that majority of TGW have dental anxiety. Therefore, it is crucial for the dental practitioner to acknowledge this finding and offer appropriate dental management in overcoming dental anxiety among TGW.